Public Private Partnerships in Chinese Hospitals and Knowledge Transfer - António, N. (Organizational Learning in Asia: Issues and Challenges, 2017)
In China today, the general consensus is that the internal public sector alone cannot satisfy the healthcare needs of the citizens, and that the joint contribution of both the private and non-profit sectors is essential to solve this problem, especially given the additional pressures arising from an ageing population. Since 1978, China ?s healthcare industry has gone through several reforms, including the application of Public- (non-profit) Private Partnerships (PPPs), and involving the introduction of market mechanisms within a “Mixed Economy” model. PPPs provide opportunities for leveraging resources that might otherwise not be available to the government alone. Therefore, it is imperative to improve our understanding of how they can be successfully introduced and managed. Through in-depth interviews, our chapter examines three PPPs involving hospitals in Guangdong, China and neighbouring Universities, in order to understand the difficulties in the process of knowledge transfer, especially involving tacit knowledge, so as to contribute to the development of more effective in these and other similar organization.